Meaning of Trade Digitalization for Dinoyo Traditional Market Traders, Malang City - Titin Nurazizah; Sunaryanto; Lisa Rokhmani (CV. AFDIFAL MAJU BERKAH, 2022)
Technological developments have an impact on the world of education, economy, social, culture and development in Indonesia. This change is the reaction of each individual in an effort to understand the various changes that occur and their consequences. The influence of technological advances introduces a new terminology about the digital economy as a new economic era. The government together with traditional market managers are intensifying trade digitization for traditional market traders. This study aims to determine the meaning of trade digitization for traditional market traders. This study uses a qualitative research method with the type of phenomenology. The number of informants in this study amounted to six traders in the Dinoyo traditional market. The selection of research subjects using purposive sampling method. The technique used in data collection in this study used the technique of observation, in-depth interviews, and documentation. The data analysis technique in this study uses data analysis stages from Creswell which include: raw data, processing and preparing data, reading all data, coding data, connecting themes, interpreting themes. Then to check the validity of the data, the researchers used source and technique triangulation. The results of this study indicate that the attitude of market traders with the digitalization of trade shows a positive and enthusiastic attitude towards trade digitization, market traders gain knowledge about trade digitization through non-formal education by participating in training held by market managers. Digital technology provides convenience and benefits for market traders in carrying out their business activities. Future researchers are expected to be able to develop further related to the research subject and expand the research area in order to obtain comprehensive results.